OPTIMIZING PT SEMEN PADANG PERFORMANCE POST-COMMERCIAL CENTRALIZATION TO THE HOLDCO - Gusman*, Muhammad Hanif; Furinto, Asnan (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
This research aims to explores the beneficial extension of the Holdco strategy and formulates the suitable meso-level strategies for PT Semen Padang. This research uses primary and secondary data collection methods, identifies the environments through generic frameworks, analyses qualitative data through thematic frameworks, and formulates the result as corporate and business strategies. According to the research, Holdco set the sales target in a top-down instruction without PT Semen Padang's interference on the procurement, marketing of cement and clinker, and supply chain functions. These functions are essential and inseparable from sales targets but withdrawn to Holdco. However, Holdco allows PT Semen Padang to develop the plant process, non-cement product, non-clinker product, and enter the non-cement business. Therefore, PT Semen Padang could fulfill the strategy gap and gain a global subsidiary mandate by building a university-industry collaboration, strengthening the vertical integration, utilizing cost-saving technologies, and the outside cement chain diversification. Keywords : Commercial Centralization, Global Subsidiary, Collaboration, Vertical Integration, Diversification